Controls of Nutrient Availability in River Ecosystems: A Case Study of Tigris River - Batool Kadhim; Mohammed Hamdan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In response to the water crisis, further research is necessary to comprehend the impact of human activities on nutrient concentrations in aquatic ecosystems, building on the extensive studies already conducted to understand these impacts on the water quality of various aquatic ecosystems. We hypothesized that human activities in the Tigris River’s catchments could alter the nutrient concentrations in the water along the river. The results showed that phosphate concentration differed significantly among the studied sites due to distributed human activities, while nitrate concentration did not. Water temperature did not affect phosphate and nitrate concentrations. We concluded that human activities on the surrounding landscapes could be more essential sources for nutrients in aquatic ecosystems than the role of ongoing climate warming. Despite the role of warming in driving nutrient availability in aquatic ecosystems, our findings suggest that studies focusing on the trophic status classification of aquatic ecosystems should take into account the various activities in the surrounding catchments.